65.4k views
3 votes
Simplify (-2x-9)(-4)​

User Glaslos
by
5.4k points

2 Answers

5 votes

Answer: The correct answer is 8x - 36.

Step-by-step explanation: I am 98% sure.

User Ken Lange
by
6.3k points
4 votes

Answer:
8x+36

Explanation:

To simplify the expression you must apply the Distributive property.

Keep on mind that:

- According to the Distributive property, the product of the difference is equal to the difference of the products:


a(b-c)=ab-ac

- Remember the multiplication of signs:

(-)(-)=+

(+)(+)=+

(-)(+)=-

Then, you obtain the following:


(-2x-9)(-4)=8x+36

User Victor Balan
by
6.6k points